N-glycosylation of immunoglobulin G predicts incident hypertension. Issue 12 (December 2021) - Kifer, Domagoj; Louca, Panayiotis; Cvetko, Ana; Deriš, Helena; Cindrić, Ana; Grallert, Harald; Peters, Annette; Polašek, Ozren; Gornik, Olga; Mangino, Massimo; Spector, Tim D.; Valdes, Ana M.; et al.
Abstract : Objectives: Glycosylation of immunoglobulin G (IgG) is an important regulator of the immune system and has been implicated in prevalent hypertension. The aim of this study is to investigate whether the IgG glycome begins to change prior to hypertension diagnosis by analysing the IgG glycome composition in a large population-based female cohort with two independent replication samples. Methods: We included 989 unrelated cases with incident hypertension and 1628 controls from the TwinsUK cohort (mean follow-up time of 6.3 years) with IgG measured at baseline by ultra-performance liquid chromatography and longitudinal BP measurement available. We replicated our findings in 106 individuals from the 10 001 Dalmatians and 729 from KORA S4. Cox regression mixed models were applied to identify changes in glycan traits preincident hypertension, after adjusting for age, mean arterial pressure, BMI, family relatedness and multiple testing (FDR < 0.1). Significant IgG-incident hypertension associations were replicated in the two independent cohorts by leveraging Cox regression mixed models in the 10 001 Dalmatians and logistic regression models in the KORA cohort. Results: We identified and replicated four glycan traits, incidence of bisecting GlcNAc, GP4, GP9 and GP21, that are predictive of incident hypertension after adjusting for confoundes and multiple testing [hazard ratio (95% CI) ranging from 0.45 (0.24–0.84) for GP21 to 2.9 (1.5–5.68) for GP4]. We then linearly combined the four replicated glycans and found that the glycan score correlated with incident hypertension, SBP and DBP. Conclusion: Our results suggest that the IgG glycome changes prior to the development of hypertension. Abstract : Supplemental Digital Content is available in the text